ETHNOMEDICINAL PLANTS AND THEIR UTILIZATION BY VILLAGERS IN KUMARAGIRI HILLS OF SALEM DISTRICT OF TAMILNADU, INDIA - Alagesaboopathi, C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The present investigation deals with the ethnomedicinal plants of Kumaragiri Hills of Salem district, Tamilnadu. The indigenous knowledge of the village dwellers, the herbal medicine practitioners and other traditional healers and the native plants used for medicinal value were collected through questionnaire and personal interviewed during field trips. The study revealed some unknown medical uses of medicinal plants. The scientific name, family, vernacular name (Tamil), part used and traditional practice of 80 species, 65 genera and families are discussed here for the treatment of various ailments. The dicotyledons are represented by 73 species of 58 genera and 37 families while monocotyledons are represented by 7 species of 7 genera and 4 families. 91.25% dicotyledons and :8.75% monocotyledons were encountered